2009
DOI: 10.1002/cjoc.200990013
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Hydrophobicity of Ionic Liquids by Partial Chlorination and Fluorination of the Cation

Abstract: Two novel hydrophobic ionic liquids (IL) with partial substitution of chlorine and fluorine in the 1-butyl-3-methylimidazolium cation (noted as [BMIM] [PF 6 ], respectively through chlorination with chlorine gas and fluorination with potassium fluoride. The position of the chlorine substitution in the resulting IL was identified using proton nuclear magnetic resonance ( 1 H NMR). The results showed that chlorination mainly took place in the imidazolium ring and partly in the methyl of butyl group. Moreover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…6 It has been reported that halogen-substituted imidazolium salts 7 and pyridinium salts 8 have characteristic crystal structures as a result of highly directional XB between the halide group and the counter anion. However, there have been few reports 4,5 of the liquid phases of the halogen-substituted imidazolium salts being characterized. This is because these compounds have high melting points owing to their high molecular weights and strong XB interactions.…”
mentioning
confidence: 99%
“…6 It has been reported that halogen-substituted imidazolium salts 7 and pyridinium salts 8 have characteristic crystal structures as a result of highly directional XB between the halide group and the counter anion. However, there have been few reports 4,5 of the liquid phases of the halogen-substituted imidazolium salts being characterized. This is because these compounds have high melting points owing to their high molecular weights and strong XB interactions.…”
mentioning
confidence: 99%
“…Note an excellent coincidence of the present results with the experiment by Wang and coworkers. 19 Chlorination of the imidazole ring and the methyl group occurs in the experiment and is thermodynamically most favorable in our simulations. For unclear reasons, chlorination of the methylene groups were not reported by Wang, possibly due to technical difficulties in identification.…”
Section: Resultsmentioning
confidence: 71%
“…Wang and coworkers 19 This work investigates halogenation (fluorination and chlorination) of the imidazoliumbased ILs from the thermodynamics perspective. We identify five chemically non-equivalent prospective halogenation sites in the 1-ethyl-3-methylimidazolium cation.…”
Section: Introductionmentioning
confidence: 99%
“…Halogenated derivatives are omnipresent in the organic synthesis, both as the end-products and in the numerous established methods for total synthesis. Fluorine, chlorine, and bromine atoms, when substituting hydrogen in the organic molecules, change chemical and physical chemical properties significantly and sometimes drastically. Many widely applied organic solvents were obtained by halogenating aliphatic hydrocarbons (gases). Modification of RTILs using halogenation is interesting for a few reasons: (1) more available solvents with slightly variable sets of properties approach an era of task-specific ionic liquids; (2) halogen atoms are able to block specific binding sites and promote additional binding sites; (3) more electronegative atoms, as compared to hydrogen, induce novel charge density distributions within a cation.…”
Section: Introductionmentioning
confidence: 99%